THE EFFECT OF JOB INSECURITY AND JOB SATISFACTION ON TURNOVER INTENTION WITH ORGANIZATIONAL COMMITMENT AS A MEDIATION VARIABLE - Radesman Radesman; Badia Perizade; Zunaidah Zunaidah (Media Mahardhika, 2023)
Study this aim for knowing the influence of job insecurity and job satisfaction on the turnover intention with organizational commitment as variable mediation on power non-PNS education at Sriwijaya University. Study this done with use approach quantitative with sample 265 power non-PNS education at Sriwijaya University. Data processing using Structural Equation Modeling (SEM) with the Smart PLS program. Measurement models in research use second-order factors. Research results show that job insecurity and job satisfaction are influential and significant to turnover intention. Organizational commitment could mediate the connection Between job insecurity and job satisfaction to turnover intention. It can be concluded that job insecurity and job satisfaction are influential direct and do not live through an organizational commitment to turnover intention on power non-PNS education at Sriwijaya University.